Clinical surgery in general RCS course manual - Kirk,R.M.; Cochrane, John, FRCS.; Kirk, R. M. (Raymond Maurice).; Mansfield, Averil O. (Edinburgh ; New York : Churchill Livingstone, 1993)
candidates are expected to be able to utilize their acquired knowledge of basic science to solve clinical problems.
this book content ; organization of accident and emergency department and major disaster plans-- wound management -- chest injuries vascular trauma -- management of burns-- rehabilitation -- neurosurgery.
Surgery. include index.
Includes bibliographical references and index.
All age.
Keywords: Surgery, Operative; Surgery